Candida glabrata Esophagitis: Are We Seeing the Emergence of a New Azole-Resistant Pathogen? - Aze Wilson; Johan Delport; Terry Ponich (International Journal of Microbiology)
Background. Candida glabrata (C. glabrata) has become a recognized pathogen in fungal esophagitis. A proportion of these isolates are azole-resistant which may have treatment implications. Variability in the prevalence of this organism exists in the limited data available. Objective. To determine the incidence of C. glabrata esophagitis in a North American hospital setting and to highlight factors that may predispose patients to this condition. Methods. Patient charts were collected from January 1, 2009 to July 30, 2011. Any charts of patients identified as having esophagitis with a positive fungal culture were reviewed for the species of Candida and the presence of factors that would predispose them to esophageal candidiasis. Results. The prevalence of Candida esophagitis based on culture was 2.2% (37 subjects). C. glabrata was the 2nd most prevalent pathogen identified (24.3% or 9 subjects). Of the C. glabrata cohort, all patients had at least one factor predisposing them to candidiasis. Conclusion. C. glabrata esophagitis makes up a large portion of the candidal esophagitis seen in hospital. C. glabrata infections were associated with at least one risk factor for candidal infection. Given its resistance to azole-based therapy, this may have treatment implications for how candidal esophagitis is approached by the clinician.